Transverse Cervical Artery Flap Repair of Benign Acquired Tracheoesophageal Fistula - Artz, Jourdain D.; Yoo, Daniel; Gilbert-Fernández, Juan José; Walvekar, Rohan R.; Risher, William H.; Dupin, Charles (Journal of Reconstructive Microsurgery Open, 2019)
Acquired tracheoesophageal fistulas are rare but associated with significant morbidity and mortality. The majority of cases are due to prolonged or complicated endotracheal intubation, tracheostomy, or esophageal malignancy, or subsequent to radiation or chemotherapy for treatment of the latter. Other etiologies include esophageal stenting and complications secondary to endoscopic procedures. The pathophysiology involves chronic inflammation of the esophagus or posterior wall of the trachea, ultimately promoting fistulization between these two structures. Risk factors primarily depend on the etiology; however, excessive balloon pressures and prolonged intubation are among the strongest predictors of acquired tracheoesophageal fistula. In two reported cases, intubation with persistent air leaks resulted in fistulization. Patients present with refractory pneumonia, aspiration, hypoxemia, acute respiratory distress, enteral feed in endotracheal aspirate, or gastric distention following extubation. It can be difficult to distinguish normal functional deterioration from deterioration secondary to intubation. Up to 51% of patients intubated for at least 48 hours may experience dysphagia following extubation. Ultimately, the diagnostic algorithm includes an esophagogram, followed by imaging with computed tomography (CT) scan, and, more recently, CT scan with three-dimensional reconstructions, a bronchoscopy, and an esophagoscopy. Spontaneous closure rarely occurs, and the primary treatment modalities include interventional therapy with stenting via bronchoscopy, esophagoscopy, or surgical correction. Surgical intervention is associated with higher risks due to surrounding vital anatomy and, often, technical challenges requiring multispecialty care. Our case study presents a novel and effective method of repairing a benign acquired tracheoesophageal fistula utilizing the transverse cervical artery flap.
Keywords: tracheoesophageal fistula; transverse cervical artery flap; repair